Potentials of a friction-induced recycling process to improve resource and energy efficiency in manufacturing technology - Borgert, Thomas; Milaege, Dennis; Schweizer, Swetlana; Homberg, Werner; Schaper, Mirko; Tröster, Thomas (International Journal of Material Forming)
Abstract Efforts to enhance sustainability in all areas of life are increasing worldwide. In the field of manufacturing technology, a wide variety of approaches are being used to improve both resource and energy efficiency. Efficiency as well as sustainability can be improved by creating a circular economy or through energy-efficient recycling processes. As part of the interdisciplinary research group "Light—Efficient—Mobile" investigations on the energy-efficient friction-induced recycling process have been carried out at the department of Forming and Machining Technology at Paderborn University. E.g. using the friction-induced recycling process, different formless solid aluminum materials can be direct recycled into semi-finished products in an energy-efficient manner. The results of investigations with regard to the influence of the geometrical shape and filling rate of the aluminum particles to be recycled as well as the rotational speed of the continuously rotating wheel are explained in this paper. In addition to the recycling of aluminum chips, aluminum particles like powders from the field of additive manufacturing are processed. Based on these results, the future potentials of solid-state recycling processes and their contribution to the circular economy are discussed. The main focus here is on future interdisciplinary research projects to achieve circularity in the manufacturing of user-individual semi-finished products as well as the possibility to selectively adjust the product properties with the continuous recycling process.
Keywords: General Materials Science

Ein Beitrag zur Etablierung von Holzwerkstoffen im strukturellen Automobilbau anhand der Vorentwicklung zweier Karosseriebauteile aus Rotbuche - Schweizer, Swetlana
Die überwiegende Nutzung von nachwachsenden Rohstoffen ist ein wichtiger Aspektzum dauerhaft nachhaltigen Wirtschaften. Dem Einsatz von Holzwerkstoffen in der Automobilindustriestehen u. a. immer noch zahlreiche Kenntnislücken zum Material- undzum Strukturverhalten unter z. B. dynamischer Belastung entgegen. Um den Kenntnisstandzu erweitern und das Potenzial der Holzwerkstoffe als nachhaltige Alternative zuden etablierten Werkstoffen zu veranschaulichen, wurden hier zwei Demonstratoren vonBauteilen der Fahrzeugkarosserie aus dem Furnierschichtholz (FSH) der Buche entwickeltund getestet. Die ausgewählte Stoßabsorptionsvorrichtung und die Sitzrückwandwurden unter der Berücksichtigung der auftretenden Lasten und der Materialparameterkonzeptioniert. Im Vordergrund standen bei der Stoßabsorptionsvorrichtung eine möglichsthohe Aufnahme von Crashenergie und bei der Sitzrückwand die fertigungstechnischenAspekte der Furnierumformung zu einer komplexen Geometrie. Die entwickeltenDemonstratoren erfüllten die im Rahmen dieser Arbeit an sie gestellten Anforderungenzufriedenstellend und wiesen zum Teil ein erhebliches Leichtbaupotenzial gegenüberden metallischen Referenzstrukturen auf. Mit dieser Arbeit wurden grundlegende Erkenntnisseüber das Verformungs- und Versagensverhalten von Strukturen aus FSH unterquasistatischer und dynamischer Belastung gewonnen, um so die möglichen Einsatzgebietedieses Holzwerkstoffes zu erweitern.

Non-linear mean-field modelling of UD composite laminates accounting for average asymmetric plasticity of the matrix, debonding and progressive failure - Cheng, C.; Wang, Z.; Jin, Z.; Ju, X.; Schweizer, Swetlana; Tröster, Thomas; Mahnken, Rolf (Composites Part B: Engineering)
As an effective and accurate method for modelling composite materials, mean-field homogenization is still not well studied in modelling non-linear and damage behaviours of UD composites. Investigated micro FE-simulations show that the matrix of UD composites exhibits different average plastic behaviour, named as average asymmetric matrix plasticity (AAMP), when the composite behaves different under shear, longitudinal and transverse loadings. In this study, a non-linear mean-field debonding model (NMFDM) combining a mean-field model and a fibre–matrix interface debonding model, is developed to simulate UD composites under consideration of AAMP, fibre–matrix interface damage and progressive failure. AAMP is considered by using so-called stress mode factor, which is expressed in terms of basic invariants of the matrix deviatoric stress tensor and is used as an indicator for detection of differences in the loading mode. The material behaviour of UD composites with imperfect interface is assumed identical as for perfect interface and stiffness reduced fibres. Progressive failure criteria are established with consideration of fibre breakage and matrix crack for different fibre orientations. As a representative example for the NMFDM, a C30/E201 UD composite is studied. To verify the model, experiments are conducted on polymers, carbon fibres and UD CFRPs. Finally, the model is applied to simulate a perforated CFRP laminate, which shows excellent prediction ability on deformation, debonding and progressive failure.
Keywords: Non-linear mean-field homogenization Average asymmetric plasticity of matrix Fibre–matrix interface debonding Micro-mechanical FE-simulation Progressive failure

Wood-based materials as a sustainable alternative for future car body construction - Schweizer, Swetlana; Akbulut Irmak, Emine Fulya; Tröster, Thomas

Modeling the Energy Absorption Characteristics of Wood Crash Elements - Akbulut Irmak, Emine Fulya; Hanses, Julius; Schweizer, Swetlana; Tröster, Thomas

Holz als Werkstoff im Automobil - Schweizer, Swetlana; Tröster, Thomas

Separation of Hybrid Structures for the Reclaim of their Single Components - Schweizer, Swetlana; Becker-Staines, Anna; Tröster, Thomas (Key Engineering Materials)
The main objective for an economic and ecological use of raw materials is the achievement of closed raw material cycles. Because of that, not only the manufacturing procedures are important during the development of new materials but also the recycling processes. Within the increased use of lightweight construction in recent years, the application of multi-material or hybrid structures reach high significance for the automotive industry. In this development, especially the carbon fibre reinforced plastics (CFRP) gained its importance. However, currently there are no recycling strategies available for hybrid structures; complete recycling processes for CFRP are still expandable. This work presents methods for separation of hybrid structures made of metal and CFRP, as well as the corresponding process windows and the boundary conditions. The separation is performed by introduction of thermal heat and the behaviour of these bonded compounds is analyzed based on shear tensile tests. The results of these studies are used to develop a complete recycling process for reclamation of hybrid structures.

Recyclingkonzepte für hybride Strukturen - Schweizer, Swetlana; Tröster, Thomas (Carbon Composites Magazin)